A cross cultural study of corporate blogs in the USA and Korea. (14th January 2008) - Jeon, Sunran; Yoon, Seong No; Kim, Jongheon
Corporate blogging is now world wide due to the potential benefits of blogging. The purpose of this study is to investigate corporate blogging in two leading countries of blogging: the USA and Korea. The framework to compare corporate blogging in two countries is corporate blogging strategies developed by Lee et al. As compared to corporate blogging strategies in the USA, top-down corporate blogging strategy IV (promotion) is mostly adopted in Korea and most companies use their blogs at the third party site. Promotion blogs have gained popularity and high readership in Korea unlike in the USA.